Regulatory standards and consequences for industry architecture: the case of UK Open Banking Research Policy - Dinckol, D; Ozcan, P; Zachariadis, M (Elsevier, 2023)
In this inductive qualitative study, we analyze the standardization efforts in the UK banking sector via Open Banking regulations. We examine the role of regulatory standards and how these standards evolve, highlight key decisions and factors in the process of standardization, and show how the standards implementation can lead to the emergence of new roles and connections in the industry architecture. We find that standardization is a continuous, multi-stakeholder process where not only formulation decisions, but also the adjustment of industry players to roadblocks in implementation cause recalibration of standards and shifts in industry architecture. We also unravel the architectural implications of data sharing and interoperability standardization both within and across industries.